Integration of geographic information systems and agricultural nonpoint-source pollution model to estimate runoff sediment of Huai Som sub-basin - Sutthasini Glawgitigul (Chulalongkorn University, 2008)
Thesis (M.Sc.)--Chulalongkorn University, 1999